Engaging From Both Sides: Facilitating a Canadian Two-Generation Prenatal-to-Three Program for Families Experiencing Vulnerability. Issue 2 (June 2020) - Ginn, Carla; Mughal, Muhammad K.; Pruett, Marsha K.; Pruett, Kyle; Perry, Robert L.; Benzies, Karen
Background: Young children living in families experiencing social vulnerability, including low income, mental illness, addictions, social isolation, and/or homelessness, are at risk of developmental delay. Two-generation programs can improve outcomes for preschool children, but underlying mechanisms and outcomes for younger children remain unclear. Purpose: We explored program facilitation and identified developmental benefits of a two-generation program beginning prenatally. Methods: In our convergent, concurrent mixed methods study, we interviewed agency staff ( n = 10) and held focus groups with parents ( n = 14). We compared child ( N = 100) development between program intake and exit as measured by the Ages and Stages Questionnaires 3rd edition. Results: Our core category, Engaging From Both Sides, included (a) Mitigating Adversity (focused codes Developing Trust, Letting Go of Fear, and Putting in the Effort); (b) Continual Learning (focused codes Staying Connected, and Taking it to the Community); (c) Fostering Families (focused codes Cultivating Optimism, and Happiness and Love); (d) Unravelling Cycles of Crisis (focused codes Advocating, and Helping Parents' Parent); and (e) Becoming Mainstream (focused codes Knowing Someone Has Your Back, and Managing Stress, Anxiety, and Anger). We found significant improvements in child Fine Motor, Problem-Solving, and Personal-Social domains between program intake and exit. Conclusions: Our study adds to existing literature regarding mechanisms of two-generation programs beginning prenatally. Mitigating effects of intergenerational adversity was the primary motivation for interaction and engagement of staff and parents in two-generation programming, which improved child development.